Influence of gender on epithelial host defence peptide gene expression under non-infected and infected conditions: A basic medical research study. Issue 1 (January 2018) - Rohleder, Nils Hagen; Wolff, Klaus-Dietrich; Heimüller, Sina; Axt, Anita; Kesting, Marco Rainer; Koerdt, Steffen; Mücke, Thomas; Rommel, Niklas
Abstract: Bacterial resistance against conventional antibiotics is increasing. This introduces challenges, for example, in the treatment of infected surgical wounds. Host defence peptides (HDP), which are endogenous peptide antibiotics, show broad-spectrum antimicrobial effectiveness. They protect the organism against pathological microorganisms. Synthetic HDP might supplement or even become alternatives to conventional antibiotics. Knowledge of their quantities under physiological and pathophysiological conditions is therefore required. The influence of gender on HDP expression is unknown. This study evaluates whether gender influences HDP expression in infected or healthy epithelium. Expression levels of HDP human beta-defensin (hBD)-1, -2 and -3 and psoriasin (S100A7) were analysed, by using real-time polymerase chain reaction, in samples of epithelium from infected surgical wounds (n = 20) and healthy epithelium (n = 14) from the neck in a basic medical research study (analytic observational design). The results demonstrated a significantly elevated expression of hBD-2, hBD-3 and psoriasin ( P  = 0.001 each) in infected epithelium compared with healthy epithelium. No difference in HDP expression levels was evident between samples from female and male patients, either within infected samples or within healthy epithelium samples. Thus, gender does not affect the cutaneous expression of the investigated HDP. This is fundamental knowledge for the study and potential use of HDP derivates as alternative antibiotic substances.